Scalable Synthesis of Mesoporous TiO(2) for Environmental Photocatalytic Applications - Petronella, Francesca (Materials (Basel), 2019)
Increasing environmental concern, related to pollution and clean energy demand, have urged the development of new smart solutions profiting from nanotechnology, including the renowned nanomaterial-assisted photocatalytic degradation of pollutants. In this framework, increasing efforts are devoted to the development of TiO(2)-based nanomaterials with improved photocatalytic activity. A plethora of synthesis routes to obtain high quality TiO(2)-based nanomaterials is currently available. Nonetheless, large-scale production and the application of nanosized TiO(2) is still hampered by technological issues and the high cost related to the capability to obtain TiO(2) nanoparticles with high reaction yield and adequate morphological and structural control. The present review aims at providing a selection of synthetic approaches suitable for large-scale production of mesoporous TiO(2)-based photocatalysts due to its unique features including high specific surface area, improved ultraviolet (UV) radiation absorption, high density of surface hydroxyl groups, and significant ability for further surface functionalization The overviewed synthetic strategies have been selected and classified according to the following criteria (i) high reaction yield, (ii) reliable synthesis scale-up and (iii) adequate control over morphological, structural and textural features. Potential environmental applications of such nanostructures including water remediation and air purification are also discussed.